Strengthening Agricultural Communities with Organic Rice Development Using the Jajar Legowo System - A. Besse Dahliana; A. Murniati; Fitriadi; Andi Rismayanti Fianda Sari; Islawati; Riskiyani; Darma; Hujemiati; Murni Djabar; Yusnan Suyuti DM; Jumardi (PT FORMOSA CENDEKIA GLOBAL, 2023)
The implementation of the non-profit program